2022
DOI: 10.1108/ijoa-09-2021-2963
|View full text |Cite
|
Sign up to set email alerts
|

Readiness for lean-sustainability in start-ups during the COVID-19 era

Abstract: Purpose This study aims to “identify”, “analyse” and “categorise” the lean-sustainability enablers for start-ups during the COVID-19 epidemic using total interpretive structural modelling (TISM). Design/methodology/approach A closed-ended questionnaire was used to collect data in addition to the scheduled interview. The TISM methodology is used to determine how the variables interact, and the matrice d’Impacts croises-multiplication applique´ a classement (MICMAC) method is used to rank and categorise the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…What were the inner machinations of actions, when and how quickly were decisions made and executed? Such studies would add to the literature on dynamic capabilities in preparedness (El Idrissi et al , 2023) and readiness (Thomas and Suresh, 2023; Sreenivasan and Suresh, 2023) for such extreme environments in the future. The conceptualization of organizational response with the dynamic capability of adaptiveness and speed of adaptations would serve as a guide and framework for such studies.…”
Section: Discussionmentioning
confidence: 99%
“…What were the inner machinations of actions, when and how quickly were decisions made and executed? Such studies would add to the literature on dynamic capabilities in preparedness (El Idrissi et al , 2023) and readiness (Thomas and Suresh, 2023; Sreenivasan and Suresh, 2023) for such extreme environments in the future. The conceptualization of organizational response with the dynamic capability of adaptiveness and speed of adaptations would serve as a guide and framework for such studies.…”
Section: Discussionmentioning
confidence: 99%
“…The usage of ISM and MICMAC analysis has been done extensively from different perspectives, more to identify the enablers and establish contextual relationships based on their driving and dependence power (Patil et al , 2023; Sreenivasan and Suresh, 2022; Sindhwani et al , 2022). The study used a closed-ended questionnaire and responses from earlier identified 28 experts to identify the impact of enabler variables on one another.…”
Section: Methodsmentioning
confidence: 99%
“…The state of the lean philosophy's adoption and awareness in Indian industry is not quite obvious and encouraging. Recently, during the covid pandemic, researchers studied about the lean sustainability in start-ups and health-care sectors (Sreenivasan and Suresh, 2023; Thomas and Suresh, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%